2018
DOI: 10.1055/s-0038-1676068
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Posterior Cruciate Ligament Avulsion during Cruciate Retaining Total Knee Arthroplasty

Abstract: During cruciate retaining (CR) total knee arthroplasty (TKA), the posterior cruciate ligament (PCL) may avulse at its insertion. The incidence of PCL avulsion fracture has not been previously studied. The aim of this study is to report on the incidence and clinical significance of intraoperative PCL avulsion during primary CR TKA and to identify potential risk factors. Our institutional joint registry was retrospectively reviewed for PCL avulsion occurring during CR TKA implanted between April 2008 and April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…And, we found older patients and female gender may be the two risk factors of PCL avulsion fracture, we believe this may be due to more osteoporotic bones in women as older [10]; however, further research is needed before making a definitive statement.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…And, we found older patients and female gender may be the two risk factors of PCL avulsion fracture, we believe this may be due to more osteoporotic bones in women as older [10]; however, further research is needed before making a definitive statement.…”
Section: Discussionmentioning
confidence: 83%
“…Some studies have drawn attention that most PCL insertions may be destroyed during tibia cutting, and which raises questions about how much PCL actually saves in a CR TKA [18,[22][23][24][25][26]. Eric Kim et al [10] studied the incidence and risk factors of PCL avulsion during CR TKA, they found the incidence is 1.7% and female gender was the only risk factor. This study only compared pre and post-operative ROMs to support their conclusions, but did not mention how the postoperative clinical outcomes of unreduced the PCL avulsion fracture was.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies that investigate patient-reported outcomes of PCL reduction in primary cruciateretaining TKA. Kim et al [7] showed that the incidence of tibial-sided PCL avulsion fractures was 1.7%, and female gender was the only risk factor. However, they did not reduce the PCL avulsion fracture and the function of PCL was assessed based on the comparison between the pre-and post-operative range of motion of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, whether to reduce the PCL avulsion fracture or not becomes a controversial issue. Kim et al [7] reported the incidence of tibial-sided PCL avulsion fracture during the primary cruciate-retaining TKA, but they did not attempt to reduce the fracture.…”
Section: Introductionmentioning
confidence: 99%